Perbedaan Self-Disclosure dan Loneliness ditinjau dari Kepribadian Ekstrovert dan Introvert pada Dewasa Awal Pengguna Media Sosial - Rahma, Fuaida; Ahyani, Latifah Nur (Indonesian Journal of Educational Counseling, 2025)
Social media users are predominantly young adults. Many young adults use social media for various purposes, such as communication, self-expression, or entertainment. However, social media use is associated with self-disclosure and loneliness in individuals, both extroverted and introverted personalities. The purpose of this study is to identify differences in self-disclosure and loneliness in young adult social media users in terms of extroverted and introverted personalities. There were 112 participants consisting of 44 extroverted individuals and 68 introverted individuals. The sampling technique in this study used purposive sampling technique. The measuring instrument used to obtain data is using the DISC test tool, self-disclosure scale, and loneliness scale. The results shows that there is a difference in self-disclosure of extroverted and introverted individuals as indicated by a p value of 0.001 (p<0.05). Meanwhile, there is no difference in loneliness between extroverted and introverted individuals as indicated by a p value of 0.051 (p>0.05).